Language learning strategies of English for specific purposes students at a public university in Malaysia - Ahamad Shah, Mohamed Ismail; Ismail, Yusof; Esa, Zaleha; Muhamad, Ainon Jariah (Canadian Centre for Science and Education, 2013)
Studies on strategy research have shown the usefulness and importance of language learning strategies (LLS) for ESL and EFL learners. However, research on content-based learners in relation to English for Academic Purposes (EAP) and English for Occupational Purposes (EOP) has yet to be undertaken. This study, therefore,investigated the learning strategies of students at a public English medium university in Malaysia. The study was mainly motivated by concerns about the standards of English of graduates of Malaysian universities. These concerns have also been expressed by the university authorities. The purpose of the research was to investigate the patterns of LLS as reported by the students according to gender, courses, and undergraduate programmes. A total of 312 students from three degree programmes participated in this study. Their learning strategies were investigated based on the Strategy Inventory for Language Learning (SILL) (Oxford, 1990). The findings of the study indicated that the students from the different degree programmes differed in the use of LLS. However, there was no statistically significant relationship between LLS and gender.